NURSING PROFESSIONALS' SICK LEAVE: CHARACTERISTICS AND ACTIONS AD-OPTED BY NURSE MANAGERS - Josimerci Ittavo Lamana Faria; Paulina Kurcgan (Universidade Federal do Paraná, 2014)
This study aimed to understand the perception of the nurse manager in relation to the event of Absence from work due to Sick Leave, the managerial actions he adopts, and the impact caused by these actions. This qualitative research involved the Chief Nurses of four inpatient units in a Teaching Hospital. The statements were analyzed using Bardin's proposal for content analysis. The study subjects perceive episodes of sick leave as a managerial problem, and managerial actions are adopted regarding the episodes of sick leave, aiming: to avoid harm to the professional's health; to monitor sick leave; to adapt the schedules of activities to the situations caused by the lack of personnel; and to adjust the duties of those professionals who return from periods of sick leave with restrictions for work. No effective change was considered in the contributors' narratives inherent to the managerial actions adopted.